2021
DOI: 10.29333/iji.2021.14216a
|View full text |Cite
|
Sign up to set email alerts
|

Professional Readiness and Efficiency of Future Physical Education Teachers

Abstract: At the present stage of education development, the requirements for professional training of future specialists are increasing. The purpose of this study is to determine the efficiency of the developed experimental program for the formation of professional readiness of future physical education teachers. Using the methods of mathematical statistics, a comparative analysis has been carried out of the efficiency of the developed program for assessing the professional readiness of physical education teachers. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Regarding the research results, it should be noted that the results of our research and the conclusions of the experimental process were consistent with the findings of other researchers (e.g., Casey & MacPhail, 2018). For instance, Botagariev et al (2021) found that future physical education teachers must have intellectual, creative and motivational components. The authors also confirm that these components are specific parts of the professional training of physical education teachers.…”
Section: Physical Education Teacher In Middle Schools: Requirements …supporting
confidence: 91%
“…Regarding the research results, it should be noted that the results of our research and the conclusions of the experimental process were consistent with the findings of other researchers (e.g., Casey & MacPhail, 2018). For instance, Botagariev et al (2021) found that future physical education teachers must have intellectual, creative and motivational components. The authors also confirm that these components are specific parts of the professional training of physical education teachers.…”
Section: Physical Education Teacher In Middle Schools: Requirements …supporting
confidence: 91%
“…Next, a similar study was also conducted by (Botagariev, 2021). The results of the study can be used in determining the level of professional readiness, developing ways to improve it and assessing its effectiveness in the world of physical education specialist training practice.…”
Section: Readiness In Social Competencementioning
confidence: 99%
“…In contrast to the two studies, this study examines the personality of prospective teachers from several aspects, including; (i) Readiness in pedagogic competence, (ii) Readiness in professional competence, (iii) Readiness in personality competence, and (iv) Readiness in social competence. This research is not only limited from the psychological aspect as carried out by (Catellani et al, 2018), and the professional aspect as carried out by (Botagariev, 2021). In this study, four indicators are used as the basis for the readiness of students or prospective physical education teachers.…”
Section: Readiness In Social Competencementioning
confidence: 99%